Critical Notes on the Acceleration Principle - Neisser, Hans (Quarterly Journal of Economics, 1954)
I. Change of output versus variation of demand, 253; capacity requirements as inducing investment, 254; the change in output as a necessary condition for induced investment, 258; the change in output as a sufficient condition of induced investment, 261. — II. The regularly progressive economy, 262; autonomous investment and equilibrium, 262; mathematical reformulation of the model, 265; generalizations, 269. — III. Concluding reflections on the acceleration principle, 272.